THE INFLUENCE OF ENGLISH ON MODERN DUTCH LANGUAGE - Eshboboyeva Sevinch Fayzulla qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
In the era of globalization, English has become a dominant global language that significantly influences other languages. One such language is Dutch, which has been experiencing rapid changes in vocabulary, structure, and everyday communication due to the growing presence of English. This paper explores how English affects the modern Dutch language, particularly in the areas of lexical borrowing, code-switching, media influence, and higher education. While the integration of English brings many benefits, including improved global communication and modern linguistic innovation, it also poses challenges related to cultural identity and the preservation of Dutch linguistic traditions. This study highlights both the advantages and disadvantages of English’s growing role in Dutch and calls for a balanced approach to language development.